Dispersive liquid–liquid microextraction with in situ derivatization coupled with gas chromatography and mass spectrometry for the determination of 4‐methylimidazole in red ginseng products containing caramel colors. Issue 17 (2nd August 2018) - Lee, Jangho; Lee, Yunyeol; Nam, Tae Gyu; Jang, Hae Won
Abstract: A rapid analytical method was developed for the determination of 4‐methylimidazole from red ginseng products containing caramel colors by using dispersive liquid–liquid microextraction with in situ derivatization followed by gas chromatography with mass spectrometry. Chloroform and acetonitrile were selected as the extraction and dispersive solvents, and based on the extraction efficiency, their optimum volumes were 200 and 100 μL, respectively. The optimum volumes of the derivatizing agent (isobutyl chloroformate) and catalyst (pyridine), pH, and concentration of NaCl in the sample solution were determined to be 25 and 100 μL, pH 7.6, and 0% w/v, respectively. Validation of the optimized method showed good linearity ( R 2 > 0.999), accuracy (≥89.86%), intra‐ (≤6.70%) and interday (≤4.17%) repeatability, limit of detection (0.96 μg/L), and limit of quantification (5.79 μg/L). The validated method was applied to quantify 4‐methylimidazole in red ginseng juices and concentrates, 4‐methylimidazole was only found in red ginseng juices containing caramel colorant (42.91–2863.4 μg/L) and detected in red ginseng concentrates containing >1% caramel colorant.